Peningkatan Kemampuan Mengemukakan Pendapat Melalui Layanan Bimbingan Kelompok - Amri, Khairul; Syahniar, Syahniar; Nirwana, Herman (Konselor, 2014)
Improving The Ability to Expression Idea Through Group Counselling Services. This research aimed to reveal the ability improvement in expression idea through group counselling services. There are two groups of students at grade X of SMA N 3 Padangsidimpuan that were choosen by using purposive sampling. Each group consist of ten students. The research finding shows that generally the group counselling services is effective to improve the ability in expression idea.